Sport Stadiums and Environmental Justice - Kellison, Timothy (Routledge Research in Sport, Culture and Society, 2023)
This book explores the local environmental impact of sports stadiums, and how that impact can disproportionately affect communities of color. Offering a series of review articles and global case studies, it illustrates what happens when sport organizations and other public and private stakeholders fail to factor environmental justice into their planning and operations processes. It opens with an historical account of environmental justice research and of research into sport and the natural environment. It then offers a series of case studies from around the world, including the United States, Canada, Kenya, South Africa, and Taiwan. These case studies are organized around key elements of environmental justice such as water and air pollution, displacement and gentrification, soil contamination, and transportation accessibility. They illustrate how major sports stadiums have contributed positively or negatively (or both) to the environmental health of the compact neighborhoods that surround them, to citizens' quality of life, and in particular to communities that have historically been subjected to unjust and inequitable environmental policy. Placing the issue of environmental justice front and center leads to a more complete understanding of the relationship between stadiums, the natural environment, and urban communities. Presenting new research with important implications for practice, this book is vital reading for anybody working in sport management, venue management, mega-event planning, environmental studies, sociology, geography, and urban and regional planning.